Latissimus Dorsi Tendon Repair - John W. Belk BA; Jonathan T. Bravman MD; Rachel M. Frank MD; Adam J. Seidl MD; Eric C. McCarty MD (SAGE Publishing, 2022)
Background: Latissimus dorsi tendon ruptures are rare injuries that can occur in overhead or throwing motions and are almost always sports related. Indications: Latissimus dorsi tendon ruptures are largely treated nonoperatively, although surgical repair is indicated for the young active patient looking to return to a high level of sport and for those with complete avulsion injuries or mid-substance tendon tears. Technique Description: Depending on the degree of tendon retraction, anteroinferior or posteroinferior axillary incision is made. After the tendon is mobilized, sutures are placed in a Krackow fashion through the bulk of the tendon, and the tendon footprint is prepared by gently decorticating the surface of the humerus, just anterior and inferior to the teres major insertion point. Two Arthrex Pec Buttons are then loaded into the superior and inferior limbs of the suture tape and 2 unicortical holes are drilled into the footprint of the insertion site. The superior button is placed first and then tensioned to allow the latissimus dorsi to be pulled to the bone. Next, the second button is placed, though this is not tensioned until later at the time of the biceps tenodesis. Finally, the procedure is visualized and well inspected to ensure appropriate location of the tendon and securing hardware. Results: After an appropriate rehabilitation protocol is followed for up to 6 months postoperatively, acute repair of a ruptured latissimus dorsi tendon allows for near to complete restoration of patient functionality and strength, with return to full activity possible within 6 to 8 months. Conclusion: Surgical repair of a ruptured latissimus dorsi tendon is effective in restoring upper extremity strength and functionality and is associated with high patient satisfaction. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.